CHITOSAN INHIBITION TEST AGAINST E. coli AND DIGESTIBILITY OF THE RATION IN THE IN-VITRO METHOD - Sahara, Eli; Sandi, Sofia; Yosi, Fitra (Universitas Tanjungpura, 2020)
Diarrhea and vomiting are often caused by E coli bacteria. E coli bacteria has a strain of Shigatoxigenic Escherichia coli (STEC), producing Shiga poisons or poisons such as Shiga (verotoxin) which are harmful and pollute nature. This strain of the E coli bacterium has a detrimental effect because it excludes one or both types of Shiga Like Toxin -1 (Stx -1) and Shiga Like Toxin-2 (Stx-2) toxins. This bacterial infection has the potential as a zoonotic agent because it has been found in feces and sheep meat, feces and beef meat, chicken feces and human feces. If this bacterial colony inceases in the digestive tract of poultry it will disturb the productivity of the livestock. Therefore it must be watched out and studied more deeply. The objectives of the study are 1) to see the inhibitory power of chitosan on the growth and development of E coli bacteria in vitro 2) the test of digestibility of dry matter (BK) and crude protein (PK) ration in vitro. The treatments given in this test are: R0 = control (without chitosan), R1 = 0.5% chitosan, R2 = 1% chitosan, R3 = 1.5% chitosan, R4 = 2% chitosan, R5 = 2.5% chitosan. The parameters measured were 1) inhibition of chitosan against E. coli growth based on clear zone diameter 2) digestibility of dry matter (BK) and crude protein (PK) ration in vitro. The results showed that the higher level of chitosan administration showed greater inhibition, which was indicated by the greater diameter of the clear zone caused. The provision of 2.5% chitosan shows medium inhibition that is has a range of 10-14 mm. The addition of a dose of 1.5% chitosan in the ration was able to increase the digestibility of dry matter by 7.86% and the digestibility of crude protein 11.20% higher than the control treatment (without chitosan). The conclusion of this study is that chitosan can inhibit the growth of E coli and improve the digestibility of dry matter (BK) and crude protein (PK) for the better.AbstrakPenyakit diare dan muntah-muntah sering disebabkan oleh bakteri E coli. Bakteri E coli memiliki strain Shigatoxigenic Escherichia coli (STEC), menghasilkan racun Shiga atau racun seperti Shiga (verotoxin) yang berbahaya dan mencemari alam. Strain dari bakteri E coli ini mempunyai efek merugikan karena mengeluarkan salah satu atau kedua jenis toxin Shiga Like Toxin -1 (Stx -1) maupun Shiga Like Toxin-2 (Stx-2). Infeksi bakteri ini berpotensi sebagai agen zoonosis karena sudah pernah ditemukan pada feses dan daging domba, feses dan daging sapi serta feses ayam dan feses manusia. Jika koloni bakteri ini tinggi dalam saluran pencernaan unggas akan mengganggu produktivitas ternak tersebut. Oleh sebab itu harus diwaspadai dan dikaji lebih mendalam. Tujuan penelitian adalah 1) melihat daya hambat kitosan terhadap pertumbuhan dan perkembangan bakteri E coli secara in vitro 2) menguji kecernaan bahan kering (BK) dan protein kasar (PK) ransum secara in vitro. Perlakuan yang diberikan dalam pengujian ini adalah: R0 = kontrol (tanpa kitosan), R1 = 0,5% kitosan, R2 = 1 % kitosan, R3 = 1,5% kitosan, R4 = 2% kitosan, R5 = 2,5% kitosan. Parameter yang diukur adalah 1) daya hambat kitosan terhadap pertumbuhan E. coli berdasarkan diameter zona bening (in vitro) 2) kecernaan bahan kering (BK) dan protein kasar (PK) ransum secara in vitro. Hasil penelitian menunjukkan bahwa semakin tinggi level pemberian kitosan menunjukkan daya hambat yang semakin besar yang ditandai oleh semakin besarnya diameter zona bening yang ditimbulkan. Pemberian 2,5% kitosan menunjukkan daya hambat sedang yaitu memiliki range 10 - 14 mm. Penambahan dosis 1,5% kitosan dalam ransum, mampu meningkatkan kecernaan bahan kering 7,86% dan kecernaan protein kasar 11,20% lebih tinggi dari perlakuan kontrol (tanpa kitosan). Kesimpulan penelitian ini adalah bahwa kitosan mampu menghambat pertumbuhan E coli dan meningkatkan kecernaan bahan kering (BK) serta protein kasar (PK) menjadi lebih baik.Kata kunci: Kitosan, daya hambat, E. coli, kecernaan ransum, in vitro